MODEL TASK-BASED LEARNING UNTUK MEMBANGUN PEMBELAJARAN MANDIRI PADA TUTORIAL ONLINE - Salwa, Athiyah (LPPM Universitas Terbuka, 2019)
Distance learning organized by Universitas Terbuka provides many benefits and opportunities for students in remote areas to get higher education services. For the time being, this learning program is facilitated by e-learning assistance program using technology and information media. This learning process emphasizes unlimited materials for students outside the main source, Buku Materi Pokok, that can be accessed whenever and wherever. The main focus of this tutorial online is to give a chance for students to learn in their free time, give them learning assistance, and measure how they understand the materials given. This emphasizes the learning process independently and autonomously. This article tries to give a new sight in this Tutorial Online about a technique or a model that can be applied. This model encompasses practices, assignments, and tasks can be done independently by students. This learning model will improve and build students’ autonomous learning by providing them with authentic yet simple tasks, practical and independent assignments.